SØMANDSKAB: Arbejdsidentitet og sikkerhedsregler hos danske sømænd - Knudsen, Fabienne (Tidsskriftet Antropologi, 2005)
Efforts to reduce accidents in seafaring have recently resulted in a proliferation of measures such as workplace assessments and checklists. Unfortunately, the demand for written procedures is perceived by many seafarers as counteracting the use of common sense, experience and professional knowledge epitomized in the concept of seamanship. “Seamanship” fits well with Dreyfus and Dreyfus’ model of skill acquisition: While novices steadily follow context-independent rules, context and experience become predominant at the expert level. In contrast to the novice, expert behaviour goes beyond analytical rationality and is situational, experience-based, and intuitive. The Aristotelian concept of phronesis adds a reflexive, social and ethical dimension to expert knowledge. Phronesis is, like expertise, contextual, experience-based knowledge; but it is also value- and action-oriented. It combines the capacity to recognize what ought to be done with the ability to do it. While phronesis rests on value rationality, “techne” (know how), another Aristotelian concept, is based on instrumental rationality and is production-oriented. Phronesis is, inter alia, choosing the proper techne for the circumstances. The seamen fear a development where techne predominates at the expanse of phronesis. The case raises several issues on which conditions and contexts are appropriate for rules and procedures to be perceived as a tool at the service of phronesis.